Pharmacological strategies to enhance adaptation in intestinal failure. Issue 2 (April 2016) - Pape, Ulrich-Frank; Maasberg, Sebastian; Pascher, Andreas
Abstract : Purpose of review: Intestinal failure because of more or less extensive resection of parts of the small and large intestine (short bowel syndrome) results from the reduction of absorptive surface of the remaining intestine and frequently results in dependence on parenteral nutrition. Parenteral nutrition, although lifesaving, is associated with short and long-term complications as well as with reduced quality of life and overall survival. Recent findings: Pharmacological enhancement of the physiological intestinal adaptive response by subcutaneous application of the glucagon-like peptide 2 analogue teduglutide results in an improved, hyperadaptive response. This is reflected by decreased parenteral calorie and fluid requirements, decreased parenteral nutrition infusion days per week including complete weaning off parenteral nutrition with complete oral autonomy, improved quality of life, and metabolic and nutritional stability. Summary: The advent of teduglutide as an authority-approved specific medication for intestinal failure in parenteral nutrition-dependent short bowel syndrome offers an effective and beneficial treatment for these patients. As a result, patients are more stable whether for medical or further surgical management including intestinal transplantation. Long-term efficacy and safety still have to be proven.